"Comparative energy and economic analysis of different vegetable oil plants for biodiesel production in India". (May 2021) - Kumar, Ajeet; Vachan Tirkey, Jeevan; Kumar Shukla, Shailendra
Abstract: Carbon emissions due to the exploitation of conventional sources of energy like coal, diesel, and petrol are the primary source of global warming. In recent years, biodiesel has emerged as one of the potential candidates, to be used as alternate and renewable source of energy, for reducing the carbon footprints. Thus, for the growth and development of biodiesel it is essential to evaluate the energy and economic output of various vegetable oil plants used to produce biodiesel. The present study aims to select the vegetable oil plants for biodiesel production in India by using the life cycle assessment (LCA) approach. This study conducts a comparative energy and economic analyses of biodiesel production from jatropha, mahua, neem, palm, coconut, karanja, jojoba, and tung. The results indicated that the net energy is positive for all the plants, where, neem was recognized as a higher energy ratio (5.5164) and energy productivity (0.0567 kg MJ −1 ), which could be deal with as a higher contributor for reducing CO2 emission (g CO2 eq/MJ) in diesel blending. Higher gross production values (222.27 R kg −1 ), gross returns (168.70 R kg −1 ), net returns (144.13 R kg −1 ), benefit to cost ratios (2.84) productivity (0.0122 kg Rs - 1) obtained for neem. Highlights: The major portion of the energy was consumed in methanol and electricity. The lower energy intensity was obtained for palm and neem. Major expenses are shared by man power, methanol, and electricity. Total production cost was low for palm (76.120 R kg −1 ) and neem (78.139 R kg −1 ). The higher value of average productivity (0.0122 kg R −1 ) and gross return (168.70 R kg −1 ) were obtained for neem.